2022
DOI: 10.1021/acs.inorgchem.2c02149
|View full text |Cite
|
Sign up to set email alerts
|

[C(NH2)3]2Zn(CO3)2: A Guanidinium-Templated Ultraviolet Nonlinear Optical Material

Abstract: A novel guanidinium-templated ultraviolet (UV) nonlinear optical zinc carbonate crystal, [C(NH 2 ) 3 ] 2 Zn(CO 3 ) 2 (GZCO), has been synthesized in a closed system at low temperatures. GZCO crystallizing in the tetragonal noncentrosymmetric nonpolar space group, P4 1 2 1 2 exhibits a three-dimensional anionic framework constructed by interconnected [Zn 6 C 6 O 32 ] 12membered ring channels with inorganic CO 3 triangles and ZnO 4 tetrahedra. Notably, the anhydrous GZCO shows a very high thermal stability among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 67 publications
(86 reference statements)
0
7
0
Order By: Relevance
“…In order to confirm this fact, DFT calculations on the dipole moments of D-1 and D-2 were performed using the Gaussian 09 package, and the results unveil that the dipole moment ( μ total = 7.14 D) of D-1 is much larger than that of D-2 ( μ total = 2.73 D) (Table S7†). Moreover, as shown in Table 1, the SHG intensities of D-1/L-1 are much larger than those of most reported SHG-active complexes, such as 1D chiral Cu( ii ) enantiomers with L R /L S ligands, 81 [Dy(dma) 5 ][W(CN) 8 ], 110 chiral R / S -FeNb enantiomers, 111 chiral YbZn 2 enantiomers, 112 chiral L/D-ZnBr 3 enantiomers, 113 (CASD) 2 MnBr 4 , 114 [(DPA)(18-crown-6)]ClO 4 , 115 chiral 2D Ag( i ) enantiomers, 80 a chiral Cu( i ) complex, 116 N*[MnCr], 117 C 2 H 10 N 2 ·Mg(H 2 PO 3 ) 2 (C 2 O 4 ), 118 [C(NH 2 ) 3 ] 2 Zn(CO 3 ) 2 , 119 ionic 1D chiral Cu( ii ) enantiomers with L R /L S ligands, 72 [Cd(en)-(1,3-dap)][AlB 5 O 10 ], 120 (morpholinium) 2 Cd 2 Cl 6 , 121 (C 4 H 10 NO)PbBr 3 , 122 [C(NH 2 ) 3 ] 3 AsO 4 ·2H 2 O, 123 and (Hdabco + )(CF 3 COO − ), 124 but slightly smaller than those of some complexes, such as a YbSe complex 125 and [(CH 3 ) 3 NCH 2 CHCH 2 ]FeCl 4 . 126 More remarkably, the SHG intensities of D-1/L-1 are even more than twice those of inorganic SHG-active materials, for example KTOH 127 and CKBFI.…”
Section: Resultsmentioning
confidence: 99%
“…In order to confirm this fact, DFT calculations on the dipole moments of D-1 and D-2 were performed using the Gaussian 09 package, and the results unveil that the dipole moment ( μ total = 7.14 D) of D-1 is much larger than that of D-2 ( μ total = 2.73 D) (Table S7†). Moreover, as shown in Table 1, the SHG intensities of D-1/L-1 are much larger than those of most reported SHG-active complexes, such as 1D chiral Cu( ii ) enantiomers with L R /L S ligands, 81 [Dy(dma) 5 ][W(CN) 8 ], 110 chiral R / S -FeNb enantiomers, 111 chiral YbZn 2 enantiomers, 112 chiral L/D-ZnBr 3 enantiomers, 113 (CASD) 2 MnBr 4 , 114 [(DPA)(18-crown-6)]ClO 4 , 115 chiral 2D Ag( i ) enantiomers, 80 a chiral Cu( i ) complex, 116 N*[MnCr], 117 C 2 H 10 N 2 ·Mg(H 2 PO 3 ) 2 (C 2 O 4 ), 118 [C(NH 2 ) 3 ] 2 Zn(CO 3 ) 2 , 119 ionic 1D chiral Cu( ii ) enantiomers with L R /L S ligands, 72 [Cd(en)-(1,3-dap)][AlB 5 O 10 ], 120 (morpholinium) 2 Cd 2 Cl 6 , 121 (C 4 H 10 NO)PbBr 3 , 122 [C(NH 2 ) 3 ] 3 AsO 4 ·2H 2 O, 123 and (Hdabco + )(CF 3 COO − ), 124 but slightly smaller than those of some complexes, such as a YbSe complex 125 and [(CH 3 ) 3 NCH 2 CHCH 2 ]FeCl 4 . 126 More remarkably, the SHG intensities of D-1/L-1 are even more than twice those of inorganic SHG-active materials, for example KTOH 127 and CKBFI.…”
Section: Resultsmentioning
confidence: 99%
“…25,[31][32][33]41 For confirming this point, we further carried out DFT calculations on the dipole moments of ionic D-1 and its molecular analogue [Cu(L R )(NO 3 ) 2 ] n by using the Gaussian 09 package. 37 As shown in 47 Ag(I) enantiomer, 26 one chiral Cu(I) complex, 48 [C (NH 2 ) 3 ] 2 Zn(CO 3 ) 2 , 49 and one chiral spin-crossover Fe 2 Nb bimetallic assembly. 50 The SHG intensities of D-1 and L-1 are smaller than those of some mononuclear lanthanide complexes with SHG-activity, such as a Dy III enantiomer 51 and a YbSe complex.…”
Section: Nlo Propertiesmentioning
confidence: 99%
“…Recently, π-conjugated planar organic moieties have been successfully developed as potential NLO-active groups due to their large polarizability anisotropy, ultrafast response time, and infinite design probabilities. When the organic moieties act as anions, for instance, the (H x C 3 N 3 Q 3 ) (3– x )– (Q = O, S; x = 0, 1, and 2) groups have been harnessed to build many SHG crystals such as Ca 3 (C 3 N 3 O 3 ) 2 (SHG: >2 × β-BaB 2 O 4 ), KLi­(HC 3 N 3 O 3 )·2H 2 O (5.3 × KDP), RE 5 (C 3 N 3 O 3 ) (OH) 12 (RE = Y, Yb, and Lu) (2.5–4.2 × KDP), and Cs 3 Cl­(HC 3 N 3 S 3 ) (11.4 × KDP). Theoretical calculations revealed that the organic moieties dominate the SHG effects of these materials. The organic groups can also function as cations, for example, the [C­(NH 2 ) 3 ] + group has been widely used as a SHG building group as in [C­(NH 2 ) 3 ] 6 (PO 4 ) 2 ·3H 2 O (3.8 × KDP), C­(NH 2 ) 3 SO 3 F (5 × KDP), and [C­(NH 2 ) 3 ] 2 [B 3 O 3 F 4 (OH)] (1.4 × KDP). , It is noticed that the pyridine and pyrimidine derivative groups featuring nitrogen-containing heteroaromatic rings could be protonated and used to build organic–inorganic hybrid SHG crystals such as [ o -C 5 H 4 NHOH] 2 [I 7 O 18 (OH)]·3H 2 O (8.5 × KDP), (C 5 H 6 ON) + (H 2 PO 4 ) − (3 × KDP), and (C 4 H 6 N 3 ) + (H 2 PO 3 ) − (2 × KDP). ,, …”
Section: Introductionmentioning
confidence: 99%